Learning-by-doing in torts: Liability and information about accident technology - Florian Baumann; Tim Friehe (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2015)
In the economic analysis of liability law, information about accident risk and how it can be influenced by precautions is commonly taken for granted. However, a profound understanding of the relationship between care and accident risk often requires learning-by-doing. In a two-period model, we examine the implications for the optimal level of care and behavior under strict liability and negligence, showing that liability law may not induce efficient incentives.
Keywords: K13; D62; D83; 330; liability rules; care incentives; accident technology